Buridan’s Sophisms, Alethic Predicates and Anaphoric Prosententialism - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность", 2022)
The article presents a unified method for diagnosis and treatment various semantic pathologies (Buridan’s sophisms, Liar-like sentences, etc.). The basis of this approach is a modified version of prosententialism, in which the terms ʽtrueʼ and ʽfalseʼ are considered as markers for the types of relations between truth values of pathological sentences. Unlike Russell-Tarski hierarchical approach, it pays tribute to the intuitive claim of the semantic universality of natural languages (their ability to express own semantics).